2013
DOI: 10.1089/end.2013.0236
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Stone Composition in Israel: Current Status and Variation with Age and Sex—A Bicenter Study

Abstract: Modern techniques of urinary stone analysis showed that the most frequent stone component in Israel is calcium oxalate monohydrate. In contrast to earlier reports and in accordance with reports from other countries, the overall frequency of uric acid is 14.5%. With age, the frequency of uric acid increases reaching 21% in persons >60 years old. A significant sex difference was noted in the distribution of calcium oxalate stones and infection stones. The classic 3:1 ratio was maintained, however.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
2
9
1
Order By: Relevance
“…We found that calcium oxalate stones (90.1% vs 86.9%, P < .001) were more common in men, while calcium phosphate (12.3% vs 9.1%, P < .001), struvite (4.1% vs 2.6%, P < .001), and cystine stones (3.2% vs 2.5%, P < .003) were more common in women. Similar findings were also observed in various stone composition studies 25,26 . Lieske et al found more calcium phosphate (25.0% vs 9.6%) and struvite stones (4.6% vs 1.8%) in women than in men, and more calcium oxalate (74.1% vs 58.1%) and uric acid stones (10.3% vs 5.5%) in men 25 .…”
Section: Discussionsupporting
confidence: 77%
“…We found that calcium oxalate stones (90.1% vs 86.9%, P < .001) were more common in men, while calcium phosphate (12.3% vs 9.1%, P < .001), struvite (4.1% vs 2.6%, P < .001), and cystine stones (3.2% vs 2.5%, P < .003) were more common in women. Similar findings were also observed in various stone composition studies 25,26 . Lieske et al found more calcium phosphate (25.0% vs 9.6%) and struvite stones (4.6% vs 1.8%) in women than in men, and more calcium oxalate (74.1% vs 58.1%) and uric acid stones (10.3% vs 5.5%) in men 25 .…”
Section: Discussionsupporting
confidence: 77%
“…It is widely accepted that urinary stones are more common in men than women, with a male:female ratio range of 1.4–2.9% . Males are at high risk of kidney stones overall, possibly because of a greater tendency for urine CaOx oversaturation and a high protein diet that favours CaOx supersaturation .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, USD was three times more common among men (23). Recent investigations suggest a decreasing disease excess in men (1,2,24).…”
Section: Sexmentioning
confidence: 99%
“…Stone composition may also vary by age and sex. Women have fewer calcium oxalate monohydrate stones and more struvite and calcium phosphate stones (23,26). Uric acid stones are more likely in men and the elderly (26).…”
Section: Sexmentioning
confidence: 99%